Swearing Is Not Caring: Swear Words in The Acehnese Culture - Tgk Maya Silviyanti; Yunisrina Qismullah Yusuf; Nurul Aina; Dian Fajrina (Proceedings of AICS - Social Sciences, 2021)
This qualitative research is aimed at analyzing taboo words spoken in one of the famous Acehnese comedy series, Eumpang Breuh. The data were taken from the episode Rumeh, from series one to series three, in which they are available on YouTube. The framework used was the one proposed by Gao (2013) who categorized taboo words into seven types: (1) bodily excretion, (2) death and diseases, (3) sex, (4) four-letter words, (5) swear words, (6) privacy, and (7) discriminatory language. The results revealed that there were 17 taboo words or phrases used and they are all categorized into the swear words type. Some utterances of swear words include “bangai troh u gue” (extremely stupid), “jak let bui‟ (chase after a pig), and “jeurawat ubee boh u” (a pimple as big as a coconut). Those examples reflect that the swear words used in the movies consist of insult, blasphemy, satire, threat, and judgment. Despite they are presented in an amusing way (i.e., jokes) in the movie series, taboo words should be avoided in social interactions in the Acehnese society because these words generate bad effects on the cultural norms.Keywords: Acehnese, taboo words, cultural norms, movie series.